2019
DOI: 10.1371/journal.pone.0213079
|View full text |Cite
|
Sign up to set email alerts
|

Cationic chitosan-propolis nanoparticles alter the zeta potential of S. epidermidis, inhibit biofilm formation by modulating gene expression and exhibit synergism with antibiotics

Abstract: Staphylococcus epidermidis , is a common microflora of human body that can cause opportunistic infections associated with indwelling devices. It is resistant to multiple antibiotics necessitating the need for naturally occurring antibacterial agents. Malaysian propolis, a natural product obtained from beehives exhibits antimicrobial and antibiofilm properties. Chitosan-propolis nanoparticles (CPNP) were prepared using Malaysian propolis and tested for their effect against S . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 41 publications
2
57
0
Order By: Relevance
“…However, on treatment with the PhotoActive + -or TBO-aPDT plus , a considerable down-regulation compared to the previous state was detected in all the examined genes. Ong et al 21 , whose study demonstrate that the propolis affects gene expression and makes it more sensitive to treatment with antibiotics. Also, the results of the present study showed that gtfC was more affected in the combination-treatment group than the other genes tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, on treatment with the PhotoActive + -or TBO-aPDT plus , a considerable down-regulation compared to the previous state was detected in all the examined genes. Ong et al 21 , whose study demonstrate that the propolis affects gene expression and makes it more sensitive to treatment with antibiotics. Also, the results of the present study showed that gtfC was more affected in the combination-treatment group than the other genes tested.…”
Section: Discussionmentioning
confidence: 99%
“…Propolis as a natural product collected by bees from various parts of plant sources is known to possess pharmacological activities, including anti-inflammatory, anticancer, antioxidant, antifungal, antiviral and antimicrobial effects 21 . Propolis nanoparticles (PNPs) are more effective in treatment because particle size decreases and the surface/volume ratio become too large.…”
mentioning
confidence: 99%
“…The addition of propolis to a rubber mixture made the material resistant to thermo-oxidative aging and ozone and protected it from biodegradation [53]. As for the new and interesting field of nanomaterials, chitosan–propolis nanoparticles, prepared using propolis from Asia, exhibited the abilities to alter the zeta potential of S. epidermidis , inhibit biofilm formation by modulating gene expression, and synergize with antibiotics [54]. Propolis/polyurethane composite nanofibers and electrospun materials have been proposed for biomedical applications [55].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies reported the synergistic antibacterial activities of different antibiotics after combinations with different metallic nanoparticles. [16][17][18][19][20] Some studies have described the reduction in the cytotoxicity of antimicrobial compounds after conjugations. 21,22 However, the potential in vivo toxicity and tissue distribution of these synthesized and conjugated silver nanoparticles have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%